2019
DOI: 10.3389/fevo.2019.00145
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Diversity Maintains Resiliency in a Frequently Disturbed Ecosystem

Abstract: Frequently disturbed ecosystems are characterized by resilience to ecological disturbances. Longleaf pine ecosystems are not only resilient to frequent fire disturbance, but this feature sustains biodiversity. We examined how fire frequency maintains beta diversity of multi-trophic interactions in longleaf pine ecosystems, as this community property provides a measure of functional redundancy of an ecosystem. We found that beta interaction diversity at small local scales is highest in the most frequently burne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Our metacommunity study, which, to our knowledge, is the 1 st to describe the physical and biological model of a river network across multiple hydrological phases at such a fine spatiotemporal scale, confirmed that the relative roles of niche-based and dispersal-based metacommunity processes change over time. We suggest that this conclusion may apply to other dynamic freshwater, terrestrial, and marine ecosystems (e.g., Gerisch 2014, Dell et al 2019.…”
Section: Discussionmentioning
confidence: 65%
“…Our metacommunity study, which, to our knowledge, is the 1 st to describe the physical and biological model of a river network across multiple hydrological phases at such a fine spatiotemporal scale, confirmed that the relative roles of niche-based and dispersal-based metacommunity processes change over time. We suggest that this conclusion may apply to other dynamic freshwater, terrestrial, and marine ecosystems (e.g., Gerisch 2014, Dell et al 2019.…”
Section: Discussionmentioning
confidence: 65%
“…However, processes such as natural disturbances (wind, bark beetles, wildfire) and human land‐use decisions also influence forest dynamics and resilience. Natural disturbances can enhance forest resilience by fostering response diversity (Dell et al., 2019) but changing natural disturbance regimes could also disrupt forest recovery and therefore reduce resilience (Hansen et al., 2018; Turner, Braziunas, Hansen, & Harvey, 2019). There is a high degree of uncertainty in projections of future disturbance regimes and disturbance interactions as climate changes.…”
Section: Discussionmentioning
confidence: 99%
“…While some links between taxonomic and functional diversity have been explored in some highly dynamic ecosystems (e.g. terrestrial communities exposed to floods or fire-adapted forest, Gerisch 2014, Dell et al 2019, these have been mostly restricted to static snapshot views of community patterns and, to date, their temporal dynamics have been overlooked.…”
Section: Introductionmentioning
confidence: 99%